(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2024)
This study focuses on the evaluation of two varieties of Sakurab (Allium chinense G. Don) under various mulching materials. Sakurab, also known as Chinese onion, holds cultural significance for the Meranao tribe in the Philippines and is traditionally processed into "palapa," a key ingredient in their recipes. Despite its cultural importance, there is a lack of scientific understanding of Sakurab’s growth and development, especially regarding the influence of mulching. The research is conducted in Saguiaran, Lanao del Sur, Philippines, and employs a randomized complete block design with two varieties (Rikit and Urder) and four mulching materials (No Mulch, Corn Stalk, Rice Straw, Plastic Mulch). The study aims to assess the growth and development of Sakurab varieties and determine the effects of different mulching materials on crop growth and yield. Results indicate significant differences in plant height between varieties, with Urder being taller. Mulching materials, especially corn stalk, significantly impact plant height, emphasizing the importance of mulching in crop management. The number of leaves per hill is influenced by both variety and mulching material, with Rikit displaying greater leaf counts. Crop stand at harvest is significantly affected by variety, mulching material, and their interactions, with corn stalk mulch contributing to higher stand counts. Vegetative yield per hectare is influenced by the interaction of variety and mulching material, with corn stalk mulch enhancing yields. Similarly, vegetative yield per hill is significantly affected by variety and mulching material, emphasizing the importance of these factors in determining crop productivity. Bulb yield per hill varies significantly between varieties and is positively influenced by corn stalk mulch. The number of bulbs per hill is significantly higher in Rikit, indicating a faster rate of bulb division. The length of bulbs is significantly longer in Urder, with corn stalk mulch contributing to increased bulb length. Moreover, understanding the morphological growth and development of Sakurab varieties and the influence of mulching materials is crucial for optimizing crop production. The study provides valuable insights into the cultural and agricultural significance of Sakurab, offering a foundation for further research and development in the Sakurab industry.